Penentuan Kadar Fenol Total pada Ekstrak Daun Tanaman Menggunakan Metode Spektroskopi NIR dan Kemometrik (Determination of Total Phenolic in Leave Extracts Using Spectroscopy NIR and Chemometric) - Fracilia Arinda Ratnasari; Lestyo Wulandari; Nia Kristiningrum (Pustaka Kesehatan, 2016)
Phenols are group which having one or more hydroxyl groups which attached in aromatic ring and are found in plants. The aim of this research was to study whether NIR and chemometric methods could be used to determine the total phenol content of leave extracts. These methods were compared to UV-Vis spectrophotometry. Phenol was extracted from plant leaves by ultrasonic and maceration. NIR spectral data of selected leave extracts were correlated with total phenol content using chemometric. In this study, the chemometric method that used for quantitative and qualitative analysis were Partial Least Square (PLS) and Linear Discriminant Analysis (LDA), respectively. The PLS R2 calibration was 0.9920369 and RMSEC was 2.0049472. In addition, the R2 of LOOCV and 2-Fold-Cross-Validation were 0.9939401 and 0.9834646, respectively. Furthermore, LDA gave accuracy of 100%. The significance of phenol total that have been measured by NIR and UV-Vis spectrophotometry was evaluated with paired samples T-test and gave no significant difference. In conclusion, total phenol content can be measured using NIR and chemometric methods.   Keywords: phenol, chemometric, LDA, NIR, PLS